Vai cair na prova de língua portuguesa? As avaliações em larga escala no Estado do Paraná e suas reverberações no ensino - Prado, Solange Marilene Melchior do (2023)
The object of this research is the analysis of the appropriation of discursive/textual genres by large-scale assessments in teaching the 9th year of basic education, from the perspective of social practice, considering the theories of Marcuschi and Bakhtin. To do this, it investigates whether large-scale evaluations; that assess only reading; called Prova Brazil/SAEB and Prova Paraná, Prova Paraná Mais/SAEP, that can lead to the adoption of school practices, with the hypothesis of neglecting the formation of the reader, definitively influencing the materialization of the curriculum and the teaching through the Portuguese Language textbook. Therefore, investigate the possible influences of tests on the 9th-grade textbook, and consequently, on teaching; as well as study the relationship between genders, with emphasis on the ideological issue, to critically describe the way they present themselves in the tests, highlighting the differences and similarities, are specific objectives of the investigation. The theoretical approach, from the perspective of discursive genres, uses Rojo (2012), Geraldi (2003, 2011), Marcuschi (2003, 2007, 2008), Menegassi (2010), and learning theory, considering the statements of Vygotsky (1993). Sources that address large-scale assessment and its impact in the classroom are also references, using Ravitch (2010, 2014, 2021), Freitas (2007, 2011, and 2018), and Spring (2018). The investigation has an analytical-descriptive nature and aims to draw inferences from the description of teaching materials. The methodology adopted is based on content analysis, proposed by Bardin (2011), observing the 9th-grade Portuguese language textbook and the Paraná and Brazil tests, producing tables with the characterization of the textual/discursive genres of the assessments. From the tables, there is a synthesis of the genres used, helping to understand the preparatory actions that schools promote for these assessments.